2020
DOI: 10.3390/app10207172
|View full text |Cite
|
Sign up to set email alerts
|

Noise Analysis in Pre-Amplifier Circuits Associated to Highly Sensitive Optically-Pumped Magnetometers for Geomagnetic Applications

Abstract: This paper analyzes the noise sources in photoelectric detection circuits with several low-noise operational amplifiers cores. The fabricated circuits are low-noise pre-amplifiers that are used for optically pumped magnetometers. In the proposed circuits, the noise levels of equivalent output voltage are calculated, and the results are in accordance with measurements. With a cooperation of several operational amplifiers, we select LT1028 from linear technologies as the core for our detection circuit, which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The results of the MEG data recorded from an empty room without participants indicated that the OPMs do produce intrinsic noise. An OPM is constructed using a laser, vapor cell, photodiode, photocurrent, electrical circuit, and other components, which may generate magnetic noise that is inherently related to the physical sensor [ 37 , 38 ]. We consider magnetic signals originating from the OPM components as intrinsic noise.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the MEG data recorded from an empty room without participants indicated that the OPMs do produce intrinsic noise. An OPM is constructed using a laser, vapor cell, photodiode, photocurrent, electrical circuit, and other components, which may generate magnetic noise that is inherently related to the physical sensor [ 37 , 38 ]. We consider magnetic signals originating from the OPM components as intrinsic noise.…”
Section: Discussionmentioning
confidence: 99%
“…An OPM is constructed with laser, vapor cell, heater, photodiode, photocurrent, electrical circuit, and other components that are used to heat the vapors. These components may generate magnetic artifacts that are related to the physical sensor [ 29 , 30 ]. We consider magnetic artifacts from the OPM itself (e.g., laser, vapor, and heater) to be intrinsic artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The testing results indicate that the magnetometric sensitivity approaches 140 fT/ √ Hz at 1 Hz, a factor of ~1.5 above the photon-shot noise limit, confirming the technological advancement and applicability of this sensor for magnetic anomaly detection applications. Compared to the published work [12,14], the cesium atomic magnetometer could have a wider operating temperature range and a higher sensitivity.…”
Section: Introductionmentioning
confidence: 91%
“…It achieved a sensitivity of approximately 1 pT/ √ Hz and a power consumption below 3 W [13]. In 2020, a cesium atomic magnetometer with a sensitivity of 0.6 pT/ √ Hz was also reported by Liu et al [14]. The G-824A and QTFM represent two technological directions in the current development of atomic magnetometers for geomagnetic applications.…”
Section: Introductionmentioning
confidence: 99%